Captive Minds: New Worlds and Old Metaphors - Castor, Laura Virginia (Nordlit, 1999)
The following essay discusses the politics of naming Native Americans at the end of the nineteenth century. At the time of the Wounded Knee massacre and the official "close" of the American geographical frontier, American mainstream identity had lost its earlier clarity. The attention to historical contextualization in particular suggests some of the ways in which the process of naming relates to the larger contested practice of shaping American national and cultural identities.